A systematic study of PESQ's behavior in simulated VoIP environment (from reference signal characteristics perspective) - Peter, Pocta; Miroslava, Mrvova; Peter, Kortis; Peter, Paluch; Martin, Vaculik (2008)
In this work, we experimentally study how behaviour of the PESQ-estimate varies with reference signal characteristics. In particular we investigate the impact of different lengths of reference signal and active speech ratios on speech quality estimation in simulated VoIP environment. These two reference signal characteristics are defined very broadly by ITU-T Recommendation P.862.3. That is reason to investigate an impact of those characteristics on speech quality estimation more in depth. We assess the variability of PESQ estimations with respect to the reference signal characteristics and network conditions and finally offer some proposals for the purpose of more accurate and reliable speech quality assessment from those reference signal characteristics point of view in IP networks.